Ediciones UAEM - Barañano Caldentey, Ana Margarita; Méndez Reyes, Salvador; Retana Ramírez, Ruperto; Gallegos Ruiz, Maria Antonia; Rodríguez Casas, Gerardo Armado; Pozos Olivares, Héctor (La Colmena, 2017)
-